PENGGUNAAN MEDIA SOSIAL SEBAGAI MEDIA PROMOSI UMKM JAMUR JANGGEL DI LAMPUNG SELATAN - Yan Aditiya Pratama; Arya Dwi Gusmantoro; Andini Julia; Syabilla Res Kianing Pasha; Muhammad Ega Ramadhan; Puput Ramadhani; Ade Del Alvi; Kadek Purnairawan; Novi Herawadi Sudibyo (Jurnal Publika Pengabdian Masyarakat, 2022)
Nowadays, the present of the competition is a challenge to be faced by all stakeholders. Especially, micro, small, and medium enterprises (MSMEs). One of the efforts of Dusun Jati Wangi A to increase the potential and resources is to increase the economic value of mushroom cultivation products. The purpose of this program is to support IT and the operation of business processes. This program supports online marketing and advertising to be shared more widely through Instagram social media, making it easier for potential consumers to learn about the product and making it more accessible for consumers to buy. Innovating in creating informational content about treatments to help potential consumers get to know Instagram better. Furthermore, Rebranding for Janggel Mushroom is to be more attractive and more potential consumers.